Natural products from plants and microorganisms: Novel therapeutics for chronic kidney disease via gut microbiota regulation - Zheng, Lin; Luo, Mingjing; Zhou, Haokui; Chen, Jianping (Frontiers in Pharmacology, 2023)
Dysbiosis of gut microbiota plays a fundamental role in the pathogenesis and development of chronic kidney disease (CKD) and its complications. Natural products from plants and microorganisms can achieve recognizable improvement in renal function and serve as an alternative treatment for chronic kidney disease patients with a long history, yet less is known on its beneficial effects on kidney injury by targeting the intestinal microbiota. In this review, we summarize studies on the effects of natural products from plants and microorganisms, including herbal medicines and their bioactive extracts, polysaccharides from plants and microorganisms, and phytochemicals, on the prevention and treatment of chronic kidney disease through targeting gut microflora. We describe the strategies of these anti-CKD effects in animal experiments including remodulation of gut microbiota structure, reduction of uremic toxins, enhancement of short-chain fatty acid (SCFA) production, regulation of intestinal inflammatory signaling, and improvement in intestinal integrity. Meanwhile, the clinical trials of different natural products in chronic kidney disease clinical practice were also analyzed and discussed. These provide information to enable a better understanding of the renoprotective effects of these effective natural products from plants and microorganisms in the treatment of chronic kidney disease. Finally, we propose the steps to prove the causal role of the intestinal microflora in the treatment of chronic kidney disease by natural products from plants and microorganisms. We also assess the future perspective that natural active products from plants and microorganisms can beneficially delay the onset and progression of kidney disease by targeting the gut flora and highlight the remaining challenges in this area. With the continuous deepening of studies in recent years, it has been proved that gut microbiota is a potential target of natural active products derived from plants and microorganisms for chronic kidney disease treatment. Fully understanding the functions and mechanisms of gut microbiota in these natural active products from plants and microorganisms is conducive to their application as an alternative therapeutic in the treatment of chronic kidney disease.